A Requirement Model for Computer Hardware Tracking System - Hisyam, Harun (2005)
The purpose of this project is to create a requirement model for Computer Hardware Tracking system for Royal Malaysia Navy. Requirement model provide a more structured and integrated guide for the development of systems. Its serves as a good starting point or reference for system developers to understand the user’s requirement which save cost, time and resources, thus, helps to decrease efforts in the system development process and increased quality of developed system. The methodology for requirement model of the CHTS derived from requirements analysis, analyze requirements and validate requirement model. System modeling and prototyping approach were used for requirement validation, while HOORA Analysis Tool (HAT) was used to validate the requirement model. Unified Modeling Language (UML) notation was adopted for the development of the requirement model. The requirement model consist of use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and supporting textual information. This requirement model provides a guideline in developing CHTS by specifies a solution that is right for the users need. As a conclusion, the requirement model created has solved the tracking problem as well as managing the computer hardware all over the units and ships in RMN. The requirement model can be improved that can be used in other organization. The requirement model also can be used by similar organization like army and air force.